Ethical Hermeneutics Engaging Individual-based Instrumental Reason: Lessons for Leaders in the Modern Social Imaginary - Dr. David Haney (Journal of Applied Hermeneutics)
An ethical hermeneutics is both of practical benefit for institutional leaders and an important response to what Charles Taylor describes as the “modern social imaginary,” or how people imagine their social existence and its underlying assumptions, which he argues is currently grounded in instrumental reason practiced by individuals, but without shared moral and evidentiary frameworks. Using Hans-Georg Gadamer’s hermeneutics, supplemented by ethical philosophers including Charles Taylor, Jeffrey Stout, and Emmanuel Levinas, the article considers the political and social issues raised by the modern social imaginary, especially in the United States, and shows how the consequences of individual-based instrumental reason can be productively engaged by a broadly conceived ethical hermeneutics. This approach provides both (1) a way to think within and engage the historicity of the current moment and (2) practical hermeneutic solutions to problems of communication and understanding faced by leaders, with examples from the author’s experience in academic leadership.